2023
DOI: 10.1088/1555-6611/acfb78
|View full text |Cite
|
Sign up to set email alerts
|

Red and green dual-wavelength Pr:LiGdF4 laser with a single birefringent filter

Junwen Bai,
Xinhua Fu

Abstract: A simultaneous continuous-wave (CW) dual-wavelength Pr:LiGdF4 laser using a single birefringent filter (BF) plate under excitation with a frequency doubled optically pumped semiconductor laser (2 ω-OPSL) was experimentally demonstrated. We calculate the wavelength-dependent loss property of the BF. By adjusting the BF plate, the spectral intensity ratio of the generated wavelengths can be maintained to be 1:1. A simultaneous CW dual-wavelength Pr:LiGdF4 laser at 604 and 523 nm is experimentally realized. For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Xia et al realized a visible dual-wavelength laser in Pr 3+ -doped lasers for the first time [42]. Bai and Fu obtained a red and green dualwavelength Pr:LiGdF 4 laser with a single birefringent filter [43]. He et al reported a tunable dual-wavelength laser operation of Pr 3+ :LiYF 4 , which was the first work of realizing dualwavelength Pr 3+ -doped laser operation in the infrared spectral range [44].…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al realized a visible dual-wavelength laser in Pr 3+ -doped lasers for the first time [42]. Bai and Fu obtained a red and green dualwavelength Pr:LiGdF 4 laser with a single birefringent filter [43]. He et al reported a tunable dual-wavelength laser operation of Pr 3+ :LiYF 4 , which was the first work of realizing dualwavelength Pr 3+ -doped laser operation in the infrared spectral range [44].…”
Section: Introductionmentioning
confidence: 99%